Mechanisms of CPT1C-Dependent AMPAR Trafficking Enhancement - Gratacòs-Batlle, Esther; Olivella, Mireia; Sánchez-Fernández, Nuria; Yefimenko, Natalia; Miguez-Cabello, Federico; Fadó, Rut; Casals, Núria; Gasull, Xavier; Ambrosio, Santiago; Soto, David (Frontiers in Molecular Neuroscience, 2018)
In neurons, AMPA receptor (AMPAR) function depends essentially on their constituent components: the pore forming and the auxiliary accompanying subunits. On the other hand, AMPAR trafficking is tightly regulated by a vast number of intracellular neuronal proteins that bind to AMPAR subunits. It has been recently shown that the interaction between the GluA1 subunit of AMPARs and CPT1C, a novel protein partner of AMPARs, is important in modulating surface expression of these ionotropic glutamate receptors. Indeed, synaptic transmission in CPT1C KO mice is diminished supporting a positive trafficking role for that protein. However, the molecular mechanisms of such modulation remain unknown although a putative role of CPT1C in depalmitoylating GluA1 has been hypothesized. Here we explore that possibility and show that CPT1C effect on AMPARs is likely due to changes in the palmitoylation state of GluA1. Based on in silico analysis, Ser 252, His 470 and Asp 474 are predicted to be the catalytic triad responsible for CPT1C palmitoyl thioesterase (PTE) activity. When these residues are mutated or when PTE activity is inhibited, the CPT1C effect on AMPAR trafficking is abolished, validating the CPT1C catalytic triad as being responsible for PTE activity on AMPAR. Moreover, the histidine residue (His 470) of CPT1C is crucial for the increase in GluA1 surface expression in neurons and the H470A mutation impairs the depalmitoylating catalytic activity of CPT1C. Finally, we show that CPT1C effect seems to be specific for this CPT1 isoform and it takes place solely at endoplasmic reticulum. This work adds another facet to the impressive degree of molecular mechanisms regulating AMPAR physiology.